Understanding and Neutralizing the Expense Prediction Bias: The Role of Accessibility, Typicality, and Skewness - Howard, Ray Charles “Chuck”; Hardisty, David J.; Sussman, Abigail B.; Lukas, Marcel F. (Journal of Marketing Research, 2022)
Consumers display an expense prediction bias in which they underpredict their future spending. The authors propose this bias occurs in large part because (1) consumers base their predictions on typical expenses that come to mind easily during prediction, (2) taken together, typical expenses lead to a prediction near the mode of a consumer's expense distribution rather than the mean, and (3) expenses display positive skew (with mode < mean). Accordingly, the authors also propose that prompting consumers to consider reasons why their expenses might be different than usual increases predictions—and therefore prediction accuracy—by bringing atypical expenses to mind. Ten studies (N = 6,044) provide support for this account of the bias and the “atypical intervention” developed to neutralize it.